2010
DOI: 10.1136/jcp.2010.077032
|View full text |Cite
|
Sign up to set email alerts
|

Surface bacteriology of venous leg ulcers and healing outcome

Abstract: Routine bacteriological culture analysis of the VLU wound surface may be used to identify diverse flora in all ulcers. However, the data generated are of no additional value as a prognostic indicator of healing outcome. The presence of C striatum may represent colonisation of non-healing VLU by normal skin flora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 21 publications
2
46
0
1
Order By: Relevance
“…Interestingly, a study on the incidence of skin colonization demonstrated that 10% (12/120) of the foot specimens collected from podiatry patients were positive for H. kunzii (including two-thirds of specimens from diabetic patients), whereas only one specimen (2%) from a healthy volunteer was positive (14). This predominance of H. kunzii was also demonstrated in venous leg ulcers where it was the fourth most frequently seen bacterial species (22%) in patient wounds, after Staphylococcus aureus (64%), Corynebacterium striatum (61%), and Pseudomonas aeruginosa (33%) (27). As reported here, patients are usually older than 57 years of age (5,13,16,17,19,21,23,24).…”
supporting
confidence: 73%
“…Interestingly, a study on the incidence of skin colonization demonstrated that 10% (12/120) of the foot specimens collected from podiatry patients were positive for H. kunzii (including two-thirds of specimens from diabetic patients), whereas only one specimen (2%) from a healthy volunteer was positive (14). This predominance of H. kunzii was also demonstrated in venous leg ulcers where it was the fourth most frequently seen bacterial species (22%) in patient wounds, after Staphylococcus aureus (64%), Corynebacterium striatum (61%), and Pseudomonas aeruginosa (33%) (27). As reported here, patients are usually older than 57 years of age (5,13,16,17,19,21,23,24).…”
supporting
confidence: 73%
“…108(1): 23-29, February 2013 Like several other multidrug-resistant (MDR) nondiphtherial Corynebacterium species, Corynebacterium striatum has been cited with increased frequency as a pathogen of nosocomial infections (Lee et al 2005), including septicaemias (Mart铆n et al 2003), pulmonary infection (Renom et al 2007, Wong et al 2010, meningitis (Weiss et al 1996), endocarditis (Oliva et al 2010), osteomyelitis (Fern谩ndez-Ayala et al 2001), septic arthritis (Scholle 2007), keratitis (Heidemann et al 1991), skin wounds (Moore et al 2010) and intrauterine infections (Boltin et al 2009). The first case of C. striatum in an uncomplicated urinary tract infection in an ambulatory patient without any other predisposing factors was recently reported (L贸pez et al 2009).…”
mentioning
confidence: 99%
“…As summarized in Table 1, several studies have shown no association between any specific bacterial species and healing outcomes. 16,[29][30][31][32][33] Among studies that show associations, there are conflicting conclusions on the relevance of many of the commonly isolated species, such as Staphylococcus aureus and Pseudomonas species, as well as anaerobes ( Table 2). Most studies of S. aureus show no association with healing delay or increased ulcer size.…”
Section: Presence Of Pathogenic Organismsmentioning
confidence: 99%
“…As summarized in Tables 1 and 2, some studies have concluded that nonhealing ulcers were more likely to have a higher microbial diversity, 23,35 but others have shown that diversity could not be used to predict healing. 14,32 For studies using DNA sequencing data, more specific ecological concepts of diversity can be used. Tuttle et al 10 used the Shannon diversity index, which takes into account the relative proportions of each species, showing that diversity was significantly higher in VLUs that were not healed by the 6-month follow-up.…”
Section: Microbial Diversitymentioning
confidence: 99%
See 1 more Smart Citation